2015
DOI: 10.1039/c5ra04365d
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal properties of microcrystalline cellulose-reinforced soy protein isolate–gelatin eco-friendly films

Abstract: Eco-friendly films containing soy protein isolate (SPI), gelatin, and microcrystalline cellulose (MCC) were made by casting. Effects of MCC content on mechanical and thermal properties of MCC-reinforced SPI-gelatin (MSG) films were studied. With the increasing of MCC content, thickness and tensile strength (TS) of MSG films increased, and the elongation at break (EB) decreased. MSG films containing 3.5% MCC (MSG3.5) had the limit values of the thickness, TS, and EB, which were 108%, 351%, and 27% of those of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 39 publications
2
27
0
Order By: Relevance
“…These suggestions could be supported by previous studies in which the thermal stability of FG films was improved by the addition of ethanolic extracts from coconut husk [14], nano-SiO2 particles [12], cinnamon, clove and star anise [53]. Similar results were also reported for soy protein isolates and gelatin films reinforced with microcrystalline cellulose [56], where the thermal stability of films was improved by the addition of cellulose. Differential scanning calorimetry (DSC) thermal parameters obtained for FG/PSP films are shown in Table 4.…”
Section: Thermal Properties Of Fg/psp Filmssupporting
confidence: 82%
See 1 more Smart Citation
“…These suggestions could be supported by previous studies in which the thermal stability of FG films was improved by the addition of ethanolic extracts from coconut husk [14], nano-SiO2 particles [12], cinnamon, clove and star anise [53]. Similar results were also reported for soy protein isolates and gelatin films reinforced with microcrystalline cellulose [56], where the thermal stability of films was improved by the addition of cellulose. Differential scanning calorimetry (DSC) thermal parameters obtained for FG/PSP films are shown in Table 4.…”
Section: Thermal Properties Of Fg/psp Filmssupporting
confidence: 82%
“…These suggestions could be supported by previous studies in which the thermal stability of FG films was improved by the addition of ethanolic extracts from coconut husk [14], nano-SiO 2 particles [12], cinnamon, clove and star anise [53]. Similar results were also reported for soy protein isolates and gelatin films reinforced with microcrystalline cellulose [56], where the thermal stability of films was improved by the addition of cellulose. of phenolic compounds with high antioxidant activity, in agreement with the TPC, DPPH, FRAP and ABTS results; b) the presence of xylan and cellulose as main polysaccharides in PSP resulting in a highly crystalline structure that could act as heat barrier by delaying the heat flow arising from an exterior source [55].…”
Section: Thermal Properties Of Fg/psp Filmssupporting
confidence: 82%
“…With the addition of MCC, amide I and II of SPI-MCC film shifted to 1626 and 1537 cm -1 , respectively, indicating the films might expose more polar groups and increase the bindings between the peptide chains [27]. Meanwhile, it was observed that composite films modified with MCC exhibited a new peak at 1160 cm -1 , which was attributed to the bending mode of C-CH2-C, suggesting the unique bands of cellulose [28]. These results demonstrated that molecular hydrogen bonding might be formed between protein molecule chains and polar groups with the modification of MCC, which resulting in a cross-linked structure and improving mechanical properties of the composite films [29].…”
Section: Structural Analysismentioning
confidence: 83%
“…The addition of MCC was from 2% to 8%. The variability of the additive resulted from the literature studies, where it was shown that a small amount of crystalline cellulose significantly increases the mechanical strength of the high protein films [20]. The samples prepared were mixed using the electric agitator CAT 30 at the speed of 300 rpm for 60 s. The moisture content of the material after mixing was 9% ± 0.2%.…”
Section: Methodsmentioning
confidence: 99%